Enzymuria in a population living near a cadmium battery plant. Issue 11 (November 1995) - Järup, L; Carlsson, M D; Elinder, C G; Hellström, L; Persson, B; Schütz, A
Abstract : OBJECTIVES–To study the body burden of cadmium and signs of tubular dysfunction in a rural population living near a closed nickel cadmium battery plant. METHODS–Cadmium and N-acetyl-beta-glucosaminidase (NAG) in urine were measured in 72 subjects who lived close to the plant. RESULTS–Residents living close to the plant had higher median urinary cadmium concentrations than those living farther away (1.01 v 0.46 nmol/mmol creatinine) and than a control group (0.2 nmol/mmol creatinine). There was a significant correlation between urinary cadmium and the excretion of NAG in urine as well as signs of tubular dysfunction in residents who excreted urinary cadmium above 0.5 nmol/mmol creatinine. CONCLUSION–Tubular dysfunction may appear in environmentally exposed subjects at lower cadmium body burdens than previously anticipated.